Minimum flow of the upper Irtysh river in the basin flat part in the Republic of Kazakhstan under anthropogenic impact - Manira Beysembaeva; Larissa Ivanovna Dubrovskaya; Valery Alekseevich Zemtsov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2016)
In Russian hydropolitics, the Irtysh as the transboundary river is the subject of different level negotiations on the issue of shared use of water resources with the Republic of Kazakhstan and China. In the result of putting in operation of the Upper-Irtysh multireservoir cascade the deterioration of environmental condition, particularly, in a floodplain which has major significance as the source of feed supplies for agricultural production, is observed in the flat part of the Irtysh basin. Therefore, it is important to analyze current condition and changes of different characteristics of hydrological regime of the river, and specifically the minimum flow. The aim of the researchis to indicate the changes of water flow regime and minimum water flow rates in the Irtysh River in the flat part of its basin (in the Republic of Kazakhstan). Research methods. The authors have applies hydrological and geographical approach to analyze standard observational data on the Irtysh flow in the cross section at Semiyarka village - a water level gauge station located directly downstream the multireservoir cascade during two time periods: in natural (1935-1959) and regulated (1967-2010) conditions. Statistical methods were applied: testing homogeneity of the means and variances using the Student t-test and the Fisher F-test, and trend significance using parametric and non-parametric criteria. Results. It is shown that water flow regulation by the Upper-Irtysh multireservoir cascade resulted in significant decrease of minimum summer monthly river discharge (by 22 %), increase of minimum winter river discharge (by 78 %), redistribution of the Irtysh flow between summer (decrease by 38 %) and winter (increase by 70 %) seasons, and, as a consequence, in deterioration of hydrological and environmental condition of the floodplain. Corresponding flow characteristics under natural conditions were used as the base for comparison.